(untitled) (Alternautas, 2023)
This article approaches livelihood alterations in Indigenous communities of the Ecuadorian Amazon as means of adaptation and resistance to socio-environmental impacts brought along by the expansion of global capitalism. The cases comprise collective Indigenous endeavors in typically capitalist sectors - tourism and mining - illustrated by the experiences of Kichwa community tourism in Shiripuno in the central Amazon, and sustainable mining in the southern Amazonian Shuar community of Congüime (Kenkuim). The aim is to unravel these emerging livelihood strategies in relation to Indigenous ethno-cultural identity. Methodologically, we rely on comparative and ethnographic work in the field with Indigenous actors, and on a theoretical framework anchored in the concepts of innovators, cultural boundary changes (Fredrik Barth), social fields of force (William Roseberry), and intercultural regimes (Fernando Galindo and Xavier Albó). In both empirical cases - Indigenous-controlled tourism and mining - communities are framing their ethnic identity to engage with, and positively reposition themselves in relation to the wider society. We hold that these endeavors must be comprehended as highly innovative, and that indigeneity and cultural boundaries can be strengthened by socio-cultural changes toward livelihoods previously considered as “unauthentic” or “non-Indigenous”. We also argue that these new livelihood orientations have (purposely) altered gender relations within the communities in benefit of women. Additionally, our cases suggest that cultural strengthening and gender empowerment, among other positive outcomes, requires a nuanced apprehension of indigeneity as a partly floating concept and instrument gaining ground amid the increasing interconnectedness of ancient traditions and capitalist modernity.